Scooby Doo! mystery of the Mist Monster - Manning, Matthew K; Neely, Scott (North Mankato, Minnesota Stone Arch, 2016)
"While Scooby-Doo and the gang visit a tourist town, the Mystery Machine vanished in a patch of thick fog. Other vehicles have gone missing as well. Mystery Inc. is on the case! But can they unravel the mystery of the Mist Monster, or will they get lost in the fog?"--Provided by publisher
A gift from book Africa
Comic strips
1 2 13 15
NEW_ZTN_GN
Keywords: Mystery and detective stories; Scooby-Doo (Fictitious character)